Functionally graded multilayer scaffolds for in vivo osteochondral tissue engineering. (15th September 2018) - Kang, Heemin; Zeng, Yuze; Varghese, Shyni
Graphical abstract: Abstract: Osteochondral tissue repair remains a significant challenge in orthopedic surgery. Tissue engineering of osteochondral tissue has transpired as a potential therapeutic solution as it can effectively regenerate bone, cartilage, and the bone-cartilage interface. While advancements in scaffold fabrication and stem cell engineering have made significant progress towards the engineering of composite tissues, such as osteochondral tissue, new approaches are required to improve the outcome of such strategies. Herein, we discuss the use of a single-unit trilayer scaffold with depth-varying pore architecture and mineral environment to engineer osteochondral tissues in vivo . The trilayer scaffold includes a biomineralized bottom layer mimicking the calcium phosphate (CaP)-rich bone microenvironment, a cryogel middle layer with anisotropic pore architecture, and a hydrogel top layer. The mineralized bottom layer was designed to support bone formation, while the macroporous middle layer and hydrogel top layer were designed to support cartilage tissue formation. The bottom layer was kept acellular and the top two layers were loaded with cells prior to implantation. When implanted in vivo, these trilayer scaffolds resulted in the formation of osteochondral tissue with a lubricin-rich cartilage surface. The osteochondral tissue formation was a result of continuous differentiation of the transplanted cells to form cartilage tissue and recruitment of endogenous cells through the mineralized bottom layer to form bone tissue. Our results suggest that integrating exogenous cell-based cartilage tissue engineering along with scaffold-driven in situ bone tissue engineering could be a powerful approach to engineer analogs of osteochondral tissue. In addition to offering new therapeutic opportunities, such approaches and systems could also advance our fundamental understanding of osteochondral tissue regeneration and repair. Statement of Significance: In this work, we describe the use of a single-unit trilayer scaffold with depth-varying pore architecture and mineral environment to engineer osteochondral tissues in vivo . The trilayer scaffold was designed to support continued differentiation of the donor cells to form cartilage tissue while supporting bone formation through recruitment of endogenous cells. When implanted in vivo, these trilayer scaffolds partially loaded with cells resulted in the formation of osteochondral tissue with a lubricin-rich cartilage surface. Approaches such as the one presented here that integrates ex vivo tissue engineering along with endogenous cell-mediated tissue engineering can have a significant impact in tissue engineering composite tissues with diverse cell populations and functionality.